2009
DOI: 10.1158/0008-5472.can-08-3992
|View full text |Cite
|
Sign up to set email alerts
|

The Cell Fate Determination Factor DACH1 Is Expressed in Estrogen Receptor-α–Positive Breast Cancer and Represses Estrogen Receptor-α Signaling

Abstract: The Dachshund (dac) gene, initially cloned as a dominant inhibitor of the Drosophila hyperactive EGFR mutant ellipse, encodes a key component of the cell fate determination pathway involved in Drosophila eye development. Analysis of more than 2,200 breast cancer samples showed improved survival by some 40 months in patients whose tumors expressed DACH1. Herein, DACH1 and estrogen receptor-α (ERα) expressions were inversely correlated in human breast cancer. DACH1 bound and inhibited ERα function. Nuclear DACH1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 59 publications
(74 citation statements)
references
References 50 publications
(57 reference statements)
1
73
0
Order By: Relevance
“…DACH1 represses ERα signaling by blocking coactivator-receptor interactions, i.e., PELP1-ERα interactions, which results in the increase in the relative abundance of HDAC1 on ERα target genes to suppress ERα transcription. Expression of ERα and DACH1 is also reported to be inversely correlated in human breast cancers [198]. Depletion of endogenous prohibitin (PHB), a tumor suppressor, is shown to enhance the expression of ERα target genes in MCF7 breast cancer cells.…”
Section: Corepressorsmentioning
confidence: 99%
See 1 more Smart Citation
“…DACH1 represses ERα signaling by blocking coactivator-receptor interactions, i.e., PELP1-ERα interactions, which results in the increase in the relative abundance of HDAC1 on ERα target genes to suppress ERα transcription. Expression of ERα and DACH1 is also reported to be inversely correlated in human breast cancers [198]. Depletion of endogenous prohibitin (PHB), a tumor suppressor, is shown to enhance the expression of ERα target genes in MCF7 breast cancer cells.…”
Section: Corepressorsmentioning
confidence: 99%
“…Similarly, low expression of scaffold attachment factors, such as SAFB1 and SAFB2, is associated with poor overall survival in patients who have not received adjuvant therapy [197]. Dachshund homolog 1 (DACH1), a cell fate decision factor, is a novel corepressor of ERα [198]. DACH1 represses ERα signaling by blocking coactivator-receptor interactions, i.e., PELP1-ERα interactions, which results in the increase in the relative abundance of HDAC1 on ERα target genes to suppress ERα transcription.…”
Section: Corepressorsmentioning
confidence: 99%
“…Moreover, DACH1 has been shown to interact with a DNA-binding sequence that resembles the FOX (Forkhead boxcontaining protein) binding site , but also counteracts the effect of Ras, ErbB2 and Myc on the cyclin D1 promoter through binding to c-Jun or CREB (Sunde et al, 2006;Wu et al, 2006Wu et al, , 2007. Because DACH1 interacts with the nuclear receptor co-repressor (NCoR), mSin3A and histone deacetylases (HDACs) (Popov et al, 2009;Song et al, 2003;Tskvitaria-Fuller et al, 2003;Wu et al, 2003a,b), the interaction of Dac with Hth might bring general co-repressors of the transcriptional machinery to the ban enhancers.…”
Section: Dac Is An Inhibitor Of Yki-hth Transcriptional Activitymentioning
confidence: 99%
“…Initially cloned as a dominant inhibitor of Ellipse in Drosophila, the mammalian DACH1 gene inhibits breast cancer cellular DNA synthesis and proliferation in cultured cells (13). DACH1 regulates gene expression of target genes in part through interacting with DNA-binding transcription factors (c-Jun, Smads, Six, and ER␣) and in part through intrinsic DNA binding (13,14,16). Recent studies have demonstrated that DACH1 conveys intrinsic DNA sequence-specific binding properties through elements resembling binding sites for the Forkhead family of proteins (17).…”
Section: /Cd24mentioning
confidence: 99%